Developing with Llama 3: Meta's Innovative and Open Large Language Model. - Villalobos, Ray (linkedin.com, 2024)
Learn how to leverage Llama 3's open-source technology for AI development, how it’s different from other LLMs, and how to work with the API for powerful language generation tasks.